2010
DOI: 10.2174/092986610789909539
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Mitogenic Agglutinin with Relatively High Thermostability from Seeds of the Variegated Shell Ginger

Abstract: An agglutinin with a molecular mass of 130 kDa has been isolated from the seeds of Alpinia zerumbet cv.'Variegata'. The isolation procedure involved anion exchange chromatography on DEAE-cellulose, affinity chromatography on Affi-gel blue gel, and gel filtration by fast protein liquid chromatography on Superdex 75. The agglutinin exhibited hemagglutinating activity toward rabbit erythrocytes which could not be inhibited by simple sugars. It was composed of four identical 32-kDa subunits with substantial N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…These phytolectins can be found in many plants. Hemagglutination assay was firstly found by the Wong et al [18] in the initial stages, this assay was tested on the erythrocytes. In this assay, Wong took the fresh samples of the blood and centrifuged them at 3000 rpm so that the erythrocytes can be centrifuged down and the left over supernatant can be discarded.…”
Section: Fig 3 Various Benefits Of Consumption Of Basil Seeds On the Health And Well-being Of Humans 110 Hemagglutination Activitymentioning
confidence: 99%
“…These phytolectins can be found in many plants. Hemagglutination assay was firstly found by the Wong et al [18] in the initial stages, this assay was tested on the erythrocytes. In this assay, Wong took the fresh samples of the blood and centrifuged them at 3000 rpm so that the erythrocytes can be centrifuged down and the left over supernatant can be discarded.…”
Section: Fig 3 Various Benefits Of Consumption Of Basil Seeds On the Health And Well-being Of Humans 110 Hemagglutination Activitymentioning
confidence: 99%
“…A total of 10 compounds – dihydro-5,6-dehydrogenated capsaicin, astragalin, querce­tin-3- O -β-D-glucoside, digalactosyldiacylglycerol, quercetin-3- O -β-D-glucuronide, 4′,6′-dihydroxy-2′-methoxyl dihydrochalcone, cardamomin, anibadimer A, 1- p -menthene-3,6-diol, and β -sitosterol – were isolated from the leaves of A. zerumbet [25]. An agglutinin with a molecular mass of 130 kDa and zerumbone, which can inhibit platelet aggregation, were isolated from A. zerumbet seeds and rhizomes, respectively [26, 27]. Ghareeb et al [20] identified 37 profiles of polyphenolics from the leaves of A. zerumbet using high-performance liquid chromatography-electrospray ionization mass spectrometry, including flavonoids (aglycones and glycosides) and benzoic and cinnamic acid derivatives, which demonstrate satisfactory anti-inflammatory, antinociceptive, and antipyretic effects in vivo.…”
Section: Potential Antiatherosclerotic Bioactive Compounds Of a Zerumentioning
confidence: 99%
“…In addition to Sepharose and Sephadex, commercially available Affi-Gel blue gel (Bio-Rad), composed of beaded, cross-linked agarose, has been used as an adsorbent matrix (Lin & Ng, 2008;Shao et al, 2011;Sharma et al, 2010;Wong et al, 2010). Further, naturally occurring cross-linked polysaccharides, which are inexpensive and simple to prepare with epichlorhydrin or divinyl sulphone, have also been extensively used as adsorbent matrices for isolating galactose-specific lectins (Lis & Sharon, 1981).…”
Section: Adsorbent Matricesmentioning
confidence: 99%